A study on the ventilation method for a factory exposed to high temperature. Issue 1 (September 2015) - Kim, Y; Lee, E; Jeong, H; Chung, H
Abstract: On this work, the importance of industrial ventilation was investigated and examined the theoretical point and problems about general ventilation of factory exposed on high temperature during summer. As a case study, the ventilation planning of the PCB etching process for an electronic company was carried out and each of those characteristics were compared by installing actual ventilation systems and measuring the changing state of the working environment in accordance with ventilation method during summer. The purpose of the study is to present an efficient ventilation method for a factory with a closed structure under high temperature environment. In summary, for a factory with a sealed structure such as the target PCB manufacturing factory in this study, the forced supply and exhaust method was the most appropriate ventilation method for maintaining a low indoor air temperature and for keeping the contaminated air of the factory below the hazardous level.